The Relationship Between Post-Training Mentoring and the Self-Reliance of Farmer Group Members in the Affordable Staple Rice Field Training Program in Nagari Koto Berapak, Pesisir Selatan Regency - Aulia Elvira; Mhd Natsir (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2026)
This study addresses the low level of independence among farmer group members following their participation in the Sawah Pokok Murah (SPM) training program in Nagari Koto Berapak, Pesisir Selatan Regency. Many farmers remain dependent on external assistance in managing agricultural practices, indicating that training outcomes have not been fully internalized. This research aims to examine the relationship between post-training assistance and farmer independence. A quantitative correlational design was applied, involving 44 farmers selected through simple random sampling from a total population of 59. Data were collected using structured questionnaires based on a Likert scale. Post-training assistance was measured through monitoring, reinforcement, empowerment, and assessment, while independence was assessed through intrapersonal, interactional, and behavioral aspects. Data were analyzed using descriptive statistics and Product Moment correlation. The findings show that post-training assistance is not optimally implemented, particularly in monitoring and reinforcement. Farmer independence is also relatively low, as indicated by continued reliance on external support. However, a significant positive relationship was found between post-training assistance and farmer independence.